Ocular Manifestations of Behçet’s Disease: An Update on Diagnostic Challenges and Disease Management - Hanna Zając (MDPI AG, 2021)
Behçet’s disease is a systemic vasculitis that affects multiple organs. The most common manifestations are oral and genital ulcerations and recurrent uveitis. Uveitis can be an initial symptom in 10–20% of cases and leads to blindness in 16–25% of patients. The management of this disease is evolving due to the clinical phenotypes recently described in the literature and increasing focus on the detection of subclinical inflammation to enable correct therapeutic decisions. The first line treatment is azathioprine, followed by various immunosuppressive and biological agents as alternatives in severe or refractory cases. This review summarizes scientific articles about the etiology of, diagnostic tools for and treatment of the ocular manifestations of Behçet’s disease available in the PubMed database from 1 January 2016 to 1 May 2021. A multidisciplinary approach is necessary to effectively prevent permanent damage and thus improve the life quality of the patients. Therefore, it is crucial to raise awareness of the common clusters of symptoms, use of modern imaging methods, such as ocular computed tomography and fluorescein angiography, and novelty treatment algorithms to enable early diagnosis and appropriate management.